(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article the influence of infrared radiation and temperature on the parameters of higher silicides of manganese on the surface of silicon created on the basis of impurity manganese atoms is studied. It is shown the possibility of creating effective thermal converters and photodetectors based on structures